On the alleged difficulties of on-farm research with livestock - McIntire, John M. (International Livestock Centre for Africa, 1986)
Presents and discusses analysis of shortcomings cited by Bernsten and Gryseels of ILCA regarding crop and livestock research programmes; includes animal mobility, lifecycle duration, lifecycle synchronization, multiple outputs, non-market inputs, size of experimental unit, producer attitudes, management variability, ownership of animals, resource attributes and target population.